Modelos Estocásticos De Elección De Compra Recurrente Aplicados En Hogares De La Ciudad De México - Laura Fischer; Jorge Espejo (European Scientific Journal, ESJ, 2018)
This paper focuses on examining the behaviors of repeated purchase, brand duplication, shared loyalty, and double risk using stochastic models of recurring purchase decision. A quantitative study was carried out using the panel technique in 60 homes in Mexico City. Within a period of 12 weeks, the recurring purchasing behavior of these households was recorded and analyzed. The results show, in a scientific way, the behavior of recurrent purchases in Mexican households.